A Cross-National Assessment of Media Reactions and Blame Finding of Student Perpetrated School Shootings - Barbieri, Nina (American journal of criminal justice, 2015)
In order to better understand the role that local and national concerns have in our understanding of and response to school shooting events, a content analysis of media coverage of school shootings perpetrated in the United States and Germany was conducted. Definitions of what constitutes a problem in need of policy responses vary between countries and across incidents, which becomes evident as cultural differences are examined. Six school shootings in two countries – the United States and Germany - were selected for comparison based on similarities in degree of violence and severity. News articles of the incidents were then examined for differences in thematic responses and reactions to the events between the two countries. Findings suggest that while media in both countries focused on individual related factors as the cause of school shootings, German reactions were more likely to call for state sponsored changes when compared to American media. Implications for understanding the role that media reaction has in affecting policy and areas for future research are discussed.